Murder, she knit [large type] - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery, 2018)
Pamela is hosting the next Knit and Nibble meeting and can't wait to liven up her otherwise empty home with colorful yarn, baking, and a little harmless gossip. She even recruits Amy Morgan, an old friend who recently moved to town, as the group's newest member. But on the night of the gathering, Amy doesn't show. Not until Pamela finds the woman dead outside--a knitting needle stabbed through the front of her handmade sweater. Someone committed murder before taking off with Amy's knitting bag, and Pamela realizes that only she can spot the deadly details hidden in mysterious skeins. But when another murder occurs, naming the culprit--and living to spin the tale--will be more difficult than Pamela ever imagined.